Cover Picture: J. Biophotonics 5/2016. Issue 5 (May 2016) - Unknown
Abstract : Modern methods of image analysis and processing are one of the cornerstones of research for biophotonic diagnostics. Rapid progress in methods for the analysis of medical images require continuous knowledge updates. This special issue shows new trends in analysis and processing with particular emphasis on imaging in visible light and infrared radiation used in an air‐puff tonometer, OCT, IR spectroscopy and Raman spectroscopy.